If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-(3x-21)=5(x-2)
We move all terms to the left:
2-(3x-21)-(5(x-2))=0
We get rid of parentheses
-3x-(5(x-2))+21+2=0
We calculate terms in parentheses: -(5(x-2)), so:We add all the numbers together, and all the variables
5(x-2)
We multiply parentheses
5x-10
Back to the equation:
-(5x-10)
-3x-(5x-10)+23=0
We get rid of parentheses
-3x-5x+10+23=0
We add all the numbers together, and all the variables
-8x+33=0
We move all terms containing x to the left, all other terms to the right
-8x=-33
x=-33/-8
x=4+1/8
| 2x+1/18=1/2 | | 158-10k=7k+5 | | 16v+3=88-v | | 397-9x=18x+19 | | 168-17v=-9v+16 | | -211-5x=-19x+13 | | 15r-4=6r+32 | | 6a-6=16+4a | | 7+4(6-5x)=19-14x | | 9k+9=18k-36 | | 8x+10=11x-5 | | 2x+5x=-7x | | 17x+13=x+77 | | 15x+2x^2=-9x+14x^2 | | -140-9v=-20v+3 | | 497-17x=10x+11 | | 31-2k=6k+7 | | 2r+7=22-3r | | 4v+15=45-v | | 8r+6=42-r | | 4n-18=11n-81 | | 2p-8=8p-20 | | 9r-19=2r+2 | | 3p-3=2p+2 | | 9k+3=13k-5 | | 0=-16T^2+85t+120 | | 4+3(y-7)=14 | | 17.54-1.8p=-18.46+2.5p-6.8p | | x2=3x−1 | | -2a+30=20 | | 6z-8z=16 | | 13-2n=-11 |